Good Corporate Governance And Financial Performance On Capital Adequacy Ratio: A Reflection Of Indonesian Conventional Banking - Agustina, Yuli; Winarno, Agung; Dyan, Ariska (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to determine the impact of good corporate governance, as well as financial performance as measured by non-performing loans, net interest margin, return on assets, and loan to deposit ratios, on the capital adequacy ratio of conventional banking in the period 2015-2019, using data from the Federal Reserve. The composite value of banking self-assessment is the indicator that was utilized to determine good corporate governance in the context of this study. The quantitative approach used in this study was combined with secondary data. Purposive sampling was used in this study to select a sample of 35 banks, which was then analyzed. The findings revealed that GCG, NPL, ROA, and LDR had no impact on CAR. This occurs because the revenues obtained by the bank are used to mitigate the bank's operational risk, and so have no effect on the bank's capital adequacy ratio (CAR). The NIM has a negative and statistically significant effect on the CAR. This is due to the fact that the NIM indicates that the quantity of loans granted is increasing, implying that the risk faced by the bank is also increasing.